THE REPRESENTATION AND PRODUCTION OF GENDER LITERACY IN PESANTREN LITERATURE: Tensions between Tradition and Modernity - Chusna, Aidatul; Setyorini, Ari; Murniati, Tri; Sholikhah, Ika Mar'atus; Kholifah, Asrofin Nur (JOURNAL OF INDONESIAN ISLAM, 2025)
This study examines the interplay of gender representation and cultural production within Indonesian pesantren literature by analyzing three novels: Dian Wisanggeni by Dian Latifa, Hati Suhita by Khilma Anis, and Dua Barista by Najhaty Sharma. Written by female authors with pesantren backgrounds, these novels highlight the tensions between tradition and modernity while advocating gender empowerment. Through textual and production analyses, supported by interviews with the authors, the research identifies central themes of gender literacy, including the portrayal of educated and independent female protagonists who challenge patriarchal norms. The findings reveal how these narratives navigate traditional pesantren hierarchies, explore the reconciliation of religious and modern identities, and address the broader societal implications of gender inequality. The study situates pesantren literature within the framework of Indonesian literary tradition and underscores its potential as a medium for enhancing gender awareness. By bridging Javanese traditions with Islamic values, these works inspire dialogue on the roles of Muslim women in both domestic and public spheres, fostering a nuanced understanding of gender dynamics in contemporary Islamic contexts.